Clinical efficacy and safety of glucosamine, chondroitin sulphate, their combination, celecoxib or placebo taken to treat osteoarthritis of the knee: 2-year results from GAIT. Issue 8 (4th June 2010) - Sawitzke, Allen D; Shi, Helen; Finco, Martha F; Dunlop, Dorothy D; Harris, Crystal L; Singer, Nora G; Bradley, John D; Silver, David; Jackson, Christopher G; Lane, Nancy E; Oddis, Chester V; Wolfe, Fred; et al.
Abstract : Background: Knee osteoarthritis (OA) is a major cause of pain and functional limitation in older adults, yet longer-term studies of medical treatment of OA are limited. Objective: To evaluate the efficacy and safety of glucosamine and chondroitin sulphate (CS), alone or in combination, as well as celecoxib and placebo on painful knee OA over 2 years. Methods: A 24-month, double-blind, placebo-controlled study, conducted at nine sites in the US ancillary to the Glucosamine/chondroitin Arthritis Intervention Trial, enrolled 662 patients with knee OA who satisfied radiographic criteria (Kellgren/Lawrence grade 2 or 3 changes and baseline joint space width of at least 2 mm). This subset continued to receive their randomised treatment: glucosamine 500 mg three times daily, CS 400 mg three times daily, the combination of glucosamine and CS, celecoxib 200 mg daily, or placebo over 24 months. The primary outcome was a 20% reduction in Western Ontario and McMaster University Osteoarthritis Index (WOMAC) pain over 24 months. Secondary outcomes included an Outcome Measures in Rheumatology/Osteoarthritis Research Society International response and change from baseline in WOMAC pain and function. Results: Compared with placebo, the odds of achieving a 20% reduction in WOMAC pain were celecoxib: 1.21, glucosamine: 1.16, combination glucosamine/CS: 0.83 and CS alone: 0.69, and were not statistically significant. Conclusions: Over 2 years, no treatment achieved a clinically important difference in WOMAC pain or function as compared with placebo. However, glucosamine and celecoxib showed beneficial but not significant trends. Adverse reactions were similar among treatment groups and serious adverse events were rare for all treatments.